Observation of GRB 221009A Early Afterglow in X-Ray/Gamma-Ray Energy Bands - Zheng, Chao; Zhang, Yan-Qiu; Xiong, Shao-Lin; Li, Cheng-Kui; Gao, He; Xue, Wang-Chen; Liu, Jia-Cong; Wang, Chen-Wei; Tan, Wen-Jun; Peng, Wen-Xi; An, Zheng-Hua; Cai, Ce; et al. (Astrophysical journal. Letters, 2024)
The early afterglow of a gamma-ray burst (GRB) can provide critical information on the jet and progenitor of the GRB. The extreme brightness of GRB 221009A allows us to probe its early afterglow in unprecedented detail. In this Letter, we report comprehensive observation results of the early afterglow of GRB 221009A (from T 0 +660 s to T 0 +1860 s, where T 0 is the Insight-HXMT/HE trigger time) in X-ray/gamma-ray energy band (from 20 keV to 20 MeV) by Insight-HXMT High Energy X-ray Telescope, GECAM-C, and Fermi/Gamma-ray Burst Monitor. We find that the spectrum of the early afterglow in 20 keV–20 MeV can be well described by a cutoff power law with an extra power law that dominates the low- and high-energy bands, respectively. The cutoff power law E peak is ∼30 keV, and the power-law photon index is ∼1.8 throughout the early afterglow phase. By fitting the light curves in different energy bands, we find that a significant achromatic break (from keV to TeV) is required at T 0 + 1246 − 26 + 27 s (i.e., 1021 s since the afterglow starting time T AG = T 0 +225 s), providing compelling evidence of a jet break. Interestingly, both the pre-break and post-break decay slopes vary with energy, and these two slopes become closer in the lower energy band, making the break less identifiable. Intriguingly, the spectrum of the early afterglow experienced a slight hardening before the break and a softening after the break. These results provide new insights into the physics of this remarkable GRB.